Publisher Correction: Shared heritability and functional enrichment across six solid cancers - Jiang, Xia; Brenner, Hermann; Burwinkel, Barbara; Chang-Claude, Jenny; Hamann, Ute; Hoffmeister, Michael; Risch, Angela (Nature Communications, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.